Conceptualizing the hydrogeothermal system at Sloquet Hot Springs on unceded St'at'imc territory in southwestern British Columbia - Van Acken, Ashley (2021)
Geothermal research in the southern Canadian Cordillera has typically focused on hot spring systems and predicting maximum temperatures at depth, estimating fluid circulation depths, and investigating the distribution of hot spring systems and their relation to major geological features that often control thermal fluid flow. Detailed fieldwork to develop local and regional conceptual models of these systems has rarely been conducted and to our best knowledge, never in partnership with a First Nations. The scope of this project was to work collaboratively with the local First Nation to conduct detailed structural, hydrologic and hydrogeologic fieldwork to develop local and regional conceptual models of Sloquet Hot Springs, on unceded St'at'imc territory. To motivate our research and provide a successful example of geoscience research in the era of reconciliation and Indigenous resurgence, we review how resource regulation, research, reconciliation, and resurgence interact in British Columbia and detail our approach to community engagement. Detailed studies resulted in the development of a working conceptual model for the hydrogeothermal system at Sloquet Hot Springs. The conceptual model synthesizes local and regional groundwater flow, observed geothermal gradients, advective and conductive heat flow, as well as permeability contrasts in the subsurface to understand thermal fluid flow at the study site. Well monitoring, development, and pumping tests revealed numerous soft zones in the subsurface as well as bulk values for high transmissivity and hydraulic conductivity. Findings from subsurface investigations suggest bedrock in the area has significant permeability and that groundwater flow is controlled by steep hydraulic gradients caused by rugged topography in the region. The annual spring flux was calculated for Sloquet Hot Springs and used to approximate the recharge area that is required to drive the system. Although the study did not identify the primary fault that conveys high-temperature fluids, the ...